The Effect of Work Motivation and Work Discipline on Employee Performance at the Regional Financial and Asset Management Agency - Astuti, Any; Alam, Iskandar Ali (LPPM STIE KRAKATAU, 2025)
This study examined the impact of work motivation and discipline on employee performance at the Regional Financial and Asset Management Agency (BPKAD) of Mesuji Regency, Indonesia. It addressed the discrepancy between receiving an unqualified audit opinion for four years and an